(untitled) (Law, State and Telecommunications Review, 2026)
[Purpose] This article examines a critical omission in Peru’s public digital transformation policies: the absence of environmental impact assessments (EIA) and sustainability criteria in the acquisition and implementation of digital public infrastructure (DPI). Although other sectors incorporate EIAs, the state’s digital ecosystem is still governed by a 2004 decree that ignores these standards. In the context of climate crisis, this omission is particularly worrying. [Methodology/approach/design] Using an exploratory qualitative methodology, the current legal framework was analyzed. This included the 2023 AI Law and its 2025 Regulation, the National Digital Transformation Policy, the General Public Procurement Law, and environmental legislation, to identify relevant gaps in sustainability and transparency. In parallel, recent technological acquisitions were reviewed through journalistic sources, transparency portals, and public information access requests. [Findings] The results reveal a concerning dissonance: while the country celebrates the approval of the first AI Law in Latin America and the recent adoption of its regulation with ethical principles, the rules governing software acquisitions remain outdated and do not consider environmental impact criteria. Furthermore, transparency obligations are focused solely on public entities, without requiring disclosure about the environmental impacts of private providers. This inconsistency limits the possibility of building an environmentally responsible DPI. [Practical implications] The study proposes updating procurement regulations, incorporating specific EIAs for digital technologies, and guaranteeing environmental transparency as a principle. This approach not only has potential for the country but also represents a concrete starting point for advancing toward more robust regional technology regulation. [Originality/value] The article is innovative in proposing that DPI should be treated like any other public infrastructure: with environmental impact assessments and sustainability standards throughout its lifecycle. Starting with the demand for sustainability from state-contracted providers can pave the way for more robust, cross-cutting regulations in the technology sector.